Islamic Legislation on Wealth Acquisition: A Critical Examination of Crypto-Currency - Kabir Olawale Paramole; Mubarak Oluwadamilola Sanni (Millah: Journal of Religious Studies, 2022)
Islamic legislation on wealth acquisition is an integral part of the Islamic economic system. Crypto-currency is a new technological development in the global financial system. This development has become a contentious issue among Islamic economists, financial experts, jurists, scholars, and institutions. Many unsuspecting Muslims are also cynical about its appropriateness or otherwise in their economic and financial activities. This paper adopted a qualitative methodology, which relied on article journals, textbooks, internet sources, and fatāwā (verdicts) of Islamic scholars and Islamic bodies. The paper also derived logical deduction and conclusion from the Qur’ān and Ahādith (sayings of Prophet Muhammad [PBUH]). The paper found that, generally, crypto-currencies are used to acquire wealth. It revealed that, some seemingly Sharī’ah compliant crypto-currencies are used to acquire wealth. Although, most crypto-currencies do not conform to the Islamic concept of wealth acquisition, the paper concluded that Sharī’ah compliant crypto-currencies should and could be better developed to accommodate Muslims and Muslim investors in their bid to acquire wealth.